Family Role Performance: Scale Development and Validation. Issue 1 (21st March 2013) - Chen, Yu‐Ping; Shaffer, Margaret; Westman, Mina; Chen, Shoshi; Lazarova, Mila; Reiche, Sebastian
Abstract : We conducted five interlocking studies to develop and validate a family role performance scale that can be used across cultures. In Study 1, we generated scale items based on interviews with individuals representing various family and work structures in the United States and Israel. In Study 2, we surveyed both US and Israeli participants to assess measurement equivalence, dimensionality, and reliability. In Study 3, we refined the items and repeated the exploratory analyses. In Studies 4 and 5, with samples from the United States and Europe, we confirmed the scale dimensionality and established convergent, discriminant, and nomological validity. We contribute to the work‐family literature by providing a valid instrument for assessing performance within the family domain.